Comparative and functional genomics of the protozoan parasite Babesia divergens highlighting the invasion and egress processes. - Luis Miguel González; Karel Estrada; Ricardo Grande; Verónica Jiménez-Jacinto; Leticia Vega-Alvarado; Elena Sevilla; Jorge de la Barrera; Isabel Cuesta; Ángel Zaballos; José Manuel Bautista; Cheryl A Lobo; Alejandro Sánchez-Flores; et al. (Public Library of Science (PLoS), 2019)
Babesiosis is considered an emerging disease because its incidence has significantly increased in the last 30 years, providing evidence of the expanding range of this rare but potentially life-threatening zoonotic disease. Babesia divergens is a causative agent of babesiosis in humans and cattle in Europe. The recently sequenced genome of B. divergens revealed over 3,741 protein coding-genes and the 10.7-Mb high-quality draft become the first reference tool to study the genome structure of B. divergens. Now, by exploiting this sequence data and using new computational tools and assembly strategies, we have significantly improved the quality of the B. divergens genome. The new assembly shows better continuity and has a higher correspondence to B. bovis chromosomes. Moreover, we present a differential expression analysis using RNA sequencing of the two different stages of the asexual lifecycle of B. divergens: the free merozoite capable of invading erythrocytes and the intraerythrocytic parasite stage that remains within the erythrocyte until egress. Comparison of mRNA levels of both stages identified 1,441 differentially expressed genes. From these, around half were upregulated and the other half downregulated in the intraerythrocytic stage. Orthogonal validation by real-time quantitative reverse transcription PCR confirmed the differential expression. A moderately increased expression level of genes, putatively involved in the invasion and egress processes, were revealed in the intraerythrocytic stage compared with the free merozoite. On the basis of these results and in the absence of molecular models of invasion and egress for B. divergens, we have proposed the identified genes as putative molecular players in the invasion and egress processes. Our results contribute to an understanding of key parasitic strategies and pathogenesis and could be a valuable genomic resource to exploit for the design of diagnostic methods, drugs and vaccines to improve the control of babesiosis.